C-Reactive Protein With Procalcitonin as a Marker of Occult Bacterial Infection in Fever Without a Focus - Hiremath, Pooja M; D, Narayanappa; H S, Rajani (Journal of Nepal Paediatric Society, 2021)
Introduction: Fever without a focus constitutes a major problem in children in the age group of three months to 36 months. Majority have viral infections but around 1.6 - 2% can have occult serious bacterial infection which needs early identification and treatment. The study was done to evaluate combination of CRP with Procalcitonin (PCT) as a marker of SBI in children (Three months - 36 months) with fever without focus in comparison with only PCT or CRP done separately. Methods: In this hospital based explorative study, 31 children between three months to 36 months of age with fever without any localising signs were enrolled. Relevant investigations were done to diagnose or rule out serious bacterial infection. Cut off of > 10 mg/dl for CRP and > 0.5 ng/ml for PCT was considered. Appropriate statistical analysis was done. Results: Among 31 recruited cases, 14 had occult serious bacterial infection with urinary tract infection being the most common cause. The combination PCT with CRP had sensitivity of 78.5%, specificity of 100%, and positive predictive value of 100% and negative predictive value of 85%. Diagnostic accuracy was 90.32% which did not have any statistically significant difference compared to PCT alone but significant compared to CRP alone. Conclusions: Combining CRP with procalcitonin did not have any added advantage over procalcitonin alone but combination of CRP and PCT and PCT alone is useful in detecting occult serious bacterial infections in children with fever without focus compared to CRP alone.